Biochar Induces Changes to Basic Soil Properties and Bacterial Communities of Different Soils to Varying Degrees at 25 mm Rainfall: More Effective on Acidic Soils - Zhang, Mengyang; Riaz, Muhammad; Zhang, Lin; El-desouki, Zeinab; Jiang, Cuncang (Frontiers in Microbiology, 2019)
Biochar and chemical fertilizer have been widely used in agriculture. Most studies have proved that they not only alter soil nutrient content, but also have an impact on soil microbial communities. However, the effects of biochar and chemical fertilizer application on the overall bacterial community in different soil types under rainfall conditions are not yet understood. We took rainfall as a fixed influencing factor and selected four typical soils of China to investigate the bacterial effects of biochar and chemical fertilizer at 25 mm rainfall, and to identify specific differential bacteria and their functions, and to explore the changes of the bacterial community structure of different soil types. The depth of simulated rainfall was 25 mm each time. Yellow-brown soil, fluvo-aquic soil, lou soil and black soil were chosen for experiment and each soil was divided into four treatments, included non-biochar and non-fertilizer (CK), fertilizer alone (F), biochar alone (C) and combination of biochar and fertilizer (FC). The results indicated that biochar and fertilizer have a more significant effect on bacterial communities in acidic soils. The amendment of biochar and fertilizer alone or together identified 3 (f_Oxalobacteraceae, f_Solibacteraceae_Subgroup_3, f_Sphingomonadaceae), 5 (f_Chitinophagaceae, f_Comamonadaceae, f_Geobacteraceae, f_norank_o_SC-I-84, f_norank_c_OPB35_soil_group), 1 (f_Blastocatellaceae_Subgroup_4) and 0 differential bacteria in yellow-brown soil, fluvo-aquic soil, lou soil and black soil by statistical test. In yellow-brown soil, the application of biochar alone increased the relative abundance of potential pathogens within the Sphingomonadaceae and reduced the relative abundance of beneficial bacteria in Solibacteraceae, but the addition of biochar and fertilizer together increased the relative abundance of some beneficial bacteria in Oxalobacteraceae. In fluvo-aquic soil, both biochar and chemical fertilizers promoted the relative abundance of some beneficial bacteria belonging to Chitinophagaceae, Comamonadaceae and Geobacteraceae that may be involved in nutrient cycling, degradation of plant residues and increase of metal tolerance. The interactions between soil bacterial communities and measured soil parameters including pH, organic matter were found to be statistically significant. Results from this study revealed that it is necessary to formulate biochar and fertilizer application schemes based on different soil types.